Myth, Symbolism, and Archetypes in Sylvia Plathâ€™s Selected Poems: A Critical Explanation - Suman, Shambhunath (Journal of Advanced Research in English & Education, 2025)
This article offers a critical explanation of the pervasive use of myth, symbolism, and archetypes in the selected poetry of Sylvia Plath. It argues that her work transcends the label of mere â€œconfessional poetryâ€ by employing a sophisticated framework of universal literary devices to articulate personal trauma and psychological struggle. This article posits that Plath does not simply reference existing myths but actively subverts them to empower her female speakers, as seen in the re-appropriation of the Lazarus myth in â€œLady Lazarusâ€ and the mythological scale of â€œThe Colossusâ€. Furthermore, the article delves into her highly personal and yet universally resonant symbolic language, where colours (black, white, and red) and natural elements (fire and water) carry a weight that mirrors the speakerâ€™s internal landscape. It also examines the powerful archetypal figuresâ€”the Victim, the Destroyer, the Trickster, and the Avenging Goddessâ€”that populate her poetic world, giving her personal narratives a timeless, ritualistic quality. The article concludes that Plathâ€™s genius lies in her ability to elevate her private suffering into a public, mythic, and archetypal drama, making her work a profound exploration of human suffering and defiant self-creation.